A brief report on ichthyofaunal diversity of Dewmai khola of Ilam district, Nepal - Limbu, Jash H.; Acharya, Geeta S.; Shrestha, Om H. (Journal of Natural History Museum, 2018)
Fish diversity of Nepal has been poorly studied or understood relative to other fauna, so a lot of study is still required to have a better fish diversity profile. We investigated ichthyofaunal diversity on one of the unexplored rivers, Dewmai Khola which lies in mid-hill region of Ilam district in eastern Nepal. Fishes were collected from three sampling sites in day time by using a cast net with the help of local fisherman. The field visits were performed from December2015 to September 2016. A total of 16 fish species belonging to 3 orders, 6 families and 11genera have been recorded. The Cypriniformes was the dominant order represented by 3families: 1) Cyprinidae with 7 species (Cirrhinus mrigala, Barilius barila, B. bendelisis, Bengalaelanga, Danio aequipinnatus, Schizothoraichthys labiatus and Garra gotyla), 2) Cobitidae with5 species (Schistura multifasciatus, S. horai, S. scaturigina, S. savona and S. rupecula) and3) Psilorhynchidae with a single species Psilorhynchus pseudecheneis. The Perciformes was represented by two families with a single species in each: Belontidae (Colisa fasciatus) and Channidae (Channa stewartii). The Siluriformes was represented by a single family Sisoridae with a single species Glyptothorax pectinopterus.